Optimasi Keamanan Hasil Enkripsi Algoritma Playfair Cipher ke dalam Kode Morse - Eko Prasetyo; Yessi Fitri Annisah Lubis (JITEKH, 2023)
Improving the security of cryptosystems is a challenge that attracts many researchers to propose and develop new cryptosystems to achieve cryptographic goals. In addition to implementing new cryptographic algorithms, the way that can be done is to modify, combine algorithms or even add other methods to improve existing cryptographic algorithms. Playfair Cipher is a cryptographic algorithm that has long been known and is still widely used and studied today. To optimize or strengthen the confidentiality of data from encryption (ciphertext) using the Playfair Cipher algorithm, research will be carried out by adding reverse operations and conversion into Morse code. This research produces a desktop-based application that can be used in optimizing the security of the encryption results of the Playfair Cipher cryptographic algorithm. From the test results on 10 data samples, it shows that the frequency of characters from the results of reverse and encryption (ciphertext) changes in value constantly along with the addition of the number of characters in the test text. However, after being converted into Morse code, it does not show any pattern of connection between the results of the Morse code conversion and plaintext. This proves that the encryption results after being converted into Morse code can increase (optimize) the security of the Playfair Cipher algorithm, because it will produce more random text and will not show patterns of connection between the results of the conversion into Morse code and the original text (plaintext).